PARAMETRIC STUDY OF AN ACTIVE SOLAR FLAT-PLATE COLLECTOR WATER HEATER (Nigerian Journal of Technology, 2019)
Monthly average daily weather data and solar radiations of Bauchi obtained from the weather data processor (Type 109 component) of TRNSYS 16 software were used as the input into the design equations coded using MATLAB programming language to determine the system characteristics and components sizes. Parametric study was carried out to study the effects and sensitivity of varying some design parameters such as collector area and number of glazing, length of collector tube and tube diameter, mass flow rate and volume of the water, air gap spacing between the absorber plate and glazing and the tube spacing and plate thickness on the system solar fraction (f). The results revealed that with collector area of 0.1m2 to 5m2 single glazing 82 % solar fraction was achieved and with double glazing, 97 % system solar fraction was achieved. Increasing the length of the tube increases the system solar fraction. This implies that as the number of turns of the flow tube increases the system solar fraction increases but the solar fraction decreases with increase in the diameter of the tank, with tank diameter of 0.1 m to 0.4m an average of 75 % system solar fraction was achieved. As the air gap increases, the top heat loss increases and decreases as the number of glazing increases, an air gap of 0.045 m (4.5 cm) to 0.05 m (5 cm) was found to be suitable for optimum system performance. Increasing the tube spacing, the system solar fraction decreases but as the plate thickness increases, the system solar fraction increases slightly. This implies that, decreasing the tube spacing leads to increase in system solar fraction. The plate thickness increase is considered very insignificant considering the system cost in relation to system performance. http://dx.doi.org/10.4314/njt.v38i4.9